Construction of Civic Knowledge about Morality through the Development of Digital-Based Learning Materials - Siregar, Cristian Agave; Rachman, Fazli (Jurnal Kewarganegaraan, 2024)
AbstractMoral education has become an urgency in shaping students' character through school learning. The purpose of this research is to produce a digital-based learning material product that is suitable for use by Pancasila Education teachers in the learning process for students. The research method used is research and development using the 4D development model consisting of the define, design, develop, and disseminate stages. Product validation will be conducted by content validator, media validator, Pancasila Education teacher, and 33 seventh-grade students. The results of the study show that moral education is a need for students to overcome deviant behavior. Teachers must also be able to create effective, efficient, and enjoyable learning activities. The developed digital-based website learning material obtained a very suitable category from the content expert validation with a score of 91%, media expert validation 98%, Pancasila Education teacher assessment 92% and was considered very interesting by students with a score of 91%. It can be concluded that the digital learning material with the material on the position, function, and application of Pancasila values is highly suitable and recommended for use in the Pancasila Education learning process.-----------------------------AbstrakPendidikan moral menjadi urgensi dalam membentuk karakter peserta didik melalui pembelajaran di sekolah. Tujuan penelitian ini yaitu untuk menghasilkan produk berupa materi pembelajaran berbasis digital yang layak digunakan oleh guru Pendidikan Pancasila dalam proses pembelajaran pada peserta didik. Jenis Penelitian yang digunakan yaitu research and development dengan menggunakan model pengembangan 4D yang terdiri dari tahap define, design, develop, dan disseminate. Uji validasi produk akan dilakukan oleh validasi materi, validasi media dan guru Pendidikan Pancasila serta siswa kelas VII sebanyak 33 siswa. Hasil penelitian menunjukkan bahwa edukasi moral menjadi kebutuhan siswa untuk mengatasi perilaku menyimpang. Guru juga harus dapat menciptakan kegiatan pembelajaran yang efektif, efisien, dan menyenangkan. Materi pembelajaran berbasis digital website yang dikembangkan memperoleh penilaian kategori sangat layak dari validasi ahli materi dengan skor 91%, validasi ahli media 98%, penilaian guru Pendidikan Pancasila 92% dan diperoleh kategori sangat menarik dari siswa dengan skor 91%. Dapat disimpulkan bahwa materi pembelajaran digital dengan matan materi kedudukan, fungsi dan penerapan nilai-nilai Pancasila sangat layak dan direkomendasikan untuk digunakan dalam proses pembelajaran Pendidikan Pancasila.